The Canadian Multiple Sclerosis Pregnancy Study: First-trimester miscarriages in women with multiple sclerosis. (March 2023) - Sadovnick, Dessa; Criscuoli, Maria; Yee, Irene; Carruthers, Robert; Schabas, Alice; Devonshire, Virginia; Smyth, Penelope
Background: There is increasing need for evidence-based data on reproduction for women with multiple sclerosis (MS). First-trimester (first 13 weeks) miscarriages are relatively common in the general population. It is therefore important to have information on the frequency with which this occurs in women with MS. Methods: The Canadian Multiple Sclerosis Pregnancy Study (CANPREG-MS) is a prospective study on women with MS who are pregnant or actively trying to conceive. As far as we are aware, this is the first study on miscarriages for this population that takes into account each woman's entire pregnancy history (i.e. before and after the MS diagnosis as well as during enrollment in CANPREG-MS). Results: There were 208 pregnancies during the study and 36 resulted in first-trimester miscarriage for a rate of 17.31%, within the expected range of 15%–20% for the general population. Conclusions: CANPREG-MS provides real world data that there does not appear to be an increase in first-trimester miscarriages for women with MS. This information will be helpful to women with MS and their healthcare providers.